Vincetoxicum junzifengense (Apocynaceae), a new species from Fujian, China: Evidence from morphological and molecular analyses - Ye, Bao-Jian; Tu, Xiong-De; Zhou, Cheng-Yuan; Liu, Bin; Cao, Xue-Fen; Chen, Shi-Pin (Phytotaxa, 2022)
Vincetoxicum junzifengense from Fujian Province in Southeast China is described and illustrated. This new species is similar to V. versicolor and V. stauntonii, but it differs by its climber life form, pubescent lanceolate leaf, triangular corolla lobe, dentate corona lobe, and ovoid pollinium. Phylogenetic analysis using the nuclear (ITS) and three plastid (trnT-L, trnG and psbA-trnH) DNA sequences reveals that V. junzifengense is close to V. versicolor and V. yonakuniense.